Essential medicines for childhood cancer in Europe: a pan-European, systematic analysis by SIOPE. Issue 12 (December 2022) - Otth, Maria; Brack, Eva; Kearns, Pamela R; Kozhaeva, Olga; Ocokoljic, Marko; Schoot, Reineke A; Vassal, Gilles; ,; Achini, Federica; Balduzzi, Adriana; Beck Popovic, Maja; Beishuizen, Auke; et al.
Summary: Background: Shortages and unequal access to anticancer medicines for children and adolescents are a reality in Europe. The aim of the European Society for Paediatric Oncology (SIOPE) Essential Anticancer Medicines Project was to provide a list of anticancer medicines that are considered essential in the treatment of paediatric cancers to help ensure their continuous access to all children and adolescents with cancer across Europe. Methods: This pan-European project, done between Jan 20, 2020, and Feb 18, 2022, was designed to be a systematic collection and review of treatment protocols and strategies that are used to treat childhood cancer in Europe. We formed 16 working groups on the basis of paediatric cancer types, and which were based on the existing SIOPE Clinical Trial Groups. Workings groups consisted of representatives from the SIOPE Clinical Trial Groups, Young SIOPE members, and senior paediatric oncology experts. Each group collected existing treatment protocols that are used to treat the respective cancer types in Europe. Medicines from the standard group of each protocol were extracted. For medicines not on the WHO Essential Medicines List for children (EMLc) 2017, working groups did a literature search to determine whether the medicines should be defined as essential, promising, or neither essential nor promising. Each group provided an individual summary, and all medicines that were considered essential by at least one group were combined in a joint list. Findings: The working groups identified 73 treatment protocols used in Europe and defined 66 medicines as essential. For several newer medicines, such as kinase inhibitors or tisagenlecleucel, the supporting evidence was insufficient to consider them essential, so these medicines were defined as promising. 25 medicines were considered promising by at least one working group. 22 (33%) of the 66 essential and none of the promising medicines were included in the WHO EMLc 2017. The WHO EMLc 2021 included two new medicines (everolimus and vinorelbine) following applications we made as a result of this project. Interpretation: Medicines that were defined as essential within this project should be available for the treatment of childhood and adolescent cancer continuously and across Europe. This list can be used to support and guide stakeholders and policy makers in negotiations on a national and European level regarding shortages, accessibility, and affordability of these medicines. Funding: None.